PERLINDUNGAN EKSPRESI BUDAYA TRADISIONAL DALAM SISTEM HUKUM KEKAYAAN INTELEKTUAL - Kholis Roisah (Faculty of Law, Universitas Diponegoro, 2014)
The exsisting law of intellectual property had enable to protect incomprehensive for against TCE cause that is difference between the characteristics of both IPR and TCE. Forms of IPR should be embodied in the idea (in material form), (novelty) and(originality), in the form of TCE can be verbal expression/oral, and idea of TCE must be contained and produced as an act and knowledge as well as specific techniques rooted cultural tradition. IPR system base on individualistic and monopolistic value, and TCE system base on comunal and sipiritual value